2018
DOI: 10.3390/ijerph15081638
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Lower Lung Fibrosis, Pleural Disease, and Lung Mass with Occupational, Household, Neighborhood, and Slate Roof-Dense Area Residential Asbestos Exposure

Abstract: This study aimed to evaluate the relationship between various asbestos exposure routes and asbestos-related disorders (ARDs). The study population comprised 11,186 residents of a metropolitan city who lived near asbestos factories, shipyards, or in slate roof-dense areas. ARDs were determined from chest X-rays indicating lower lung fibrosis (LFF), pleural disease (PD), and lung masses (LMs). Of the subjects, 11.2%, 10.4%, 67.2% and 8.3% were exposed to asbestos via occupational, household, neighborhood, and sl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…A few studies have reported the effects of exposure to residential asbestos-cement slate roofs on health. In a previous study using the same data as this study, the odds ratio (OR) value of lower lung fibrosis was 5.5 (3.3~9.0), pleural disease was 8.8 (5.6~13.8), lung mass was 20.5 (10.4~40.4) in residents of asbestos-cement slate roof houses and living in asbestos-cement slate dense areas [ 16 ].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…A few studies have reported the effects of exposure to residential asbestos-cement slate roofs on health. In a previous study using the same data as this study, the odds ratio (OR) value of lower lung fibrosis was 5.5 (3.3~9.0), pleural disease was 8.8 (5.6~13.8), lung mass was 20.5 (10.4~40.4) in residents of asbestos-cement slate roof houses and living in asbestos-cement slate dense areas [ 16 ].…”
Section: Discussionmentioning
confidence: 73%
“…The results derived from the pooled analysis were combined with the data from a health impact survey conducted from 2009 to 2016 at the Environmental Health Center for Asbestos (EHCA) of the Yangsan Pusan National University Hospital, South Korea, and a carcinogenic risk assessment was performed [ 16 ]. Out of a total of 11,191 subjects, 1228 people were classified into an asbestos-cement slate exposed group.…”
Section: Methodsmentioning
confidence: 99%
“…Even a high level of environmental exposure (living near asbestos mines or asbestos factories, families of asbestos workers, and others) can result in mild or early asbestosis (either grade 1 or 2 lesions or early UIP-type fibrosis) [50][51][52][53][54][55]. From these previous studies [50][51][52][53][54][55], it is not clear whether such a level of exposure causes grade 4 asbestosis or diffuse UIP-type fibrosis.…”
Section: Lower Limit Of Asbestos Fiber Exposure Causing Asbestosis Anmentioning
confidence: 99%
“…In 2018, Kang et al demonstrated an association between living in an area with a high density of asbestos roofing and lower lung fibrosis and pleural disease; however, this study was not controlled for potential confounders. 41 The studies on environmental health risks from proximity to ACR make no reference to the condition or disturbance of the ACM, and it is likely that the predominant exposure from ACR would have arisen from natural weathering.…”
Section: Health Risks From Passive Environmental Emissionsmentioning
confidence: 99%